Complex burial histories of Apollo 12 basaltic soil grains derived from cosmogenic noble gases: Implications for local regolith evolution and future in situ investigations. (7th February 2022) - Nottingham, Mark C.; Stuart, Finlay M.; Chen, Biying; Zurakowska, Marta; Gilmour, Jamie D.; Alexander, Louise; Crawford, Ian A.; Joy, Katherine H.
Abstract: We report the concentrations and isotope ratios of light noble gases (He, Ne, Ar) in 10 small basalt fragments derived from lunar regolith soils at the Apollo 12 landing site. We use cosmic ray exposure (CRE) and shielding condition histories to consider their geological context. We have devised a method of using cosmogenic Ne isotopes to partition the CRE history of each sample into two stages: a duration of "deep" burial (shielding of 5–500 g cm −2 ) and a duration of near‐surface exposure (shielding of 0 g cm −2 ). Three samples show evidence of measurable exposure at the lunar surface (durations of between 6 ± 2 and 7 ± 2 Myr). The remaining seven samples show evidence of a surface residence duration of less than a few hundred thousand years prior to collection. One sample records a single‐stage CRE age range of between 516 ± 36 and 1139 ± 121 Myr, within 0–5 g cm −2 of the lunar surface. This is consistent with derivation from ballistic sedimentation (i.e., local regolith reworking) during the Copernicus crater formation impact at 800 Myr. The remaining samples show CRE age clusters around 124 ± 11 Myr and 188 ± 15 Myr. We infer that local impacts, including Surveyor crater (180–240 Ma) and Head crater (144 Ma), may have brought these samples to depths where the cosmic ray flux was intense enough to produce measurable cosmogenic Ne isotopes. More recent small impacts that formed unnamed craters may have exhumed these samples from their deep shielding conditions to the surface (i.e., 0–5 g cm −2 ) prior to collection from the lunar surface during the Apollo 12 mission.